How Organizational Culture Moderate the Effect of Total Productive Maintenance Practice on Organization’s Operational Performance? Evidences from Indonesian Mining Industry - Nasar Buntu Laulita; Agustinus Setyawan (Jurnal Optimasi Sistem Industri, 2021)
The industry needed a system to support its operation when most of the processes were done by equipment or machines. Total Productive Maintenance (TPM) was a system to ensure all equipment or machines run in optimal performance for long period by fully supported by top management until the bottom level. Implementation of this system in the mining industry was still seldom due to some factors and organizational culture was one of the reasons. The purpose of this research was to analyze the influence of TPM implementation on operational performance by moderating the effect of organizational culture in the mining industry by using a two-step approach of structural equation model (SEM). The research type was under explanative research with hypothesis testing from primary data that was obtained from distributing questionnaires and direct interviews in the field which was analyzed by using Lisrel 8.7. This research showed that the construct of TPM has a significant impact to influence operation performance directly in the mining industry with a t-value of 3.54 and organization culture also increases the significance by moderating effect with t-value of interaction 5.28 was higher than 1.96 while organizational culture was not significant to influence operational performance directly that was showed by t-value 1.22. This research had a novelty for studying TPM practice in Indonesian mining by using SEM to analyze the moderating effect of organizational culture. The managerial implication of this research was a guideline for decision-makers to implement TPM by considering developing, group, hierarchical, and rationale culture to improve operational performance in the Indonesian mining industry.